The education of selves :how psychology transformed students - Martin, Jack, 1950-; McLellan, Ann-Marie. (New York : Oxford University Press, 2013)
This title examines the role that psychology (especially educational psychology) played in the transformation of American and Canadian classrooms and schools into sites for the self-development of students, creating an ideal image of the successful student as self-expressive, enterprising, and entitled to forms of education that recognize and cater to such expressivity and enterprise.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Jan. 7, 2013).
Keywords: Educational psychology; Transformative learning; Self-actualization (Psychology)